#### Question

Show that x = −3 is a solution of x^{2} + 6x + 9 = 0.

#### Solution

Given that the equation x^{2} + 6x + 9 = 0.

`x^2 + 3x + 3x + 9 = 0`

x (x+3) + 3 (x+3) = 0

(x + 3) (x+3) = 0

(x + 3)^{2} = 0

Square root both side, we get

(x+3) = 0

x = -3

Therefore, x = -3 is the solution of given equation.

Hence, proved.

Is there an error in this question or solution?

#### APPEARS IN

Solution Show that X = −3 is a Solution of X2 + 6x + 9 = 0. Concept: Solutions of Quadratic Equations by Factorization.